2017
DOI: 10.1002/pc.24713
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gas barrier and thermal properties of polyimide/montmorillonite nanocomposites as a result of “dual‐plane” structure effect

Abstract: A type of highly exfoliated, dispersed, and oriented organic montmorillonite filled polyimide (DABPI/OMMT) nanocomposites has been prepared successfully via in situ polymerization. Compared with the pristine DABPI, the DABPI/OMMT nanocomposites exhibit much better barrier and thermal performance. The water vapor permeability and oxygen permeability of DABPI/OMMT (5 wt%) are low to 0.31 g mil m−2 day−1 and 0.72 cm3 mil m−2 day−1, respectively. Meanwhile, its 5% weight‐loss temperature and coefficient of thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…They will lead to worse water/oxygen permeability, even though the water/oxygen permeability is always a pain point of CPI. The usual methods to solve this problem is coating barriers like SiN x O y [74] and Al 2 O 3 [75] or using composite fillers like graphene [75], montmorillonite [76], and other nanosheet fillers. Nanocomposite filler method is more practical in industrial production and can reduce the thermal expansion of CPI while keeping its transparency and thermal properties, so it is a more promising way in the future.…”
Section: Coefficient Of Linear Thermal Expansion (Cte)mentioning
confidence: 99%
“…They will lead to worse water/oxygen permeability, even though the water/oxygen permeability is always a pain point of CPI. The usual methods to solve this problem is coating barriers like SiN x O y [74] and Al 2 O 3 [75] or using composite fillers like graphene [75], montmorillonite [76], and other nanosheet fillers. Nanocomposite filler method is more practical in industrial production and can reduce the thermal expansion of CPI while keeping its transparency and thermal properties, so it is a more promising way in the future.…”
Section: Coefficient Of Linear Thermal Expansion (Cte)mentioning
confidence: 99%
“…Liu et al investigated the gas barrier and thermal properties of polyimide/graphene and polyimide/clay nanocomposites. They reported decreased water vapor transmission rates and improvement in the temperature of decomposition at 5% weight loss, concluding that addition of these nanofillers improved the thermal stability of the polyimide [ 16 , 17 ]. Wang et al observed an improvement in the mechanical, thermal, and hydrophobic properties of amino-functionalized graphene oxide/polyimide composite films.…”
Section: Introductionmentioning
confidence: 99%
“…While such strict performance requirements cannot be achieved by traditional high-barrier polymeric materials, the excellent heat resistance of PI makes it a promising substrate candidate [ 10 , 11 ]. However, the application of traditional PI as an OLED substrate is limited by its low barrier properties [ 12 , 13 ]. Fortunately, it is possible to synthesise PI with high barrier properties thanks to its excellent structural designability [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%